Tracing the Trialectic: The Process and Influence of Three Laws in the Establishment of Religious Courts in Indonesia - Moh. Muafiqul Khalid MD; Aldi Hidayat; Muhammad Alan Juhri; Elvina Lintang Solehah (Faculty of Sharia UIN Kiai Ageng Muhammad Besari Ponorogo, 2024)
This article discusses the legal trialectic in establishing the Religious Courts in Indonesia. Since its establishment in 1882, the Religious Courts have not fully represented Islamic law as its primary source. To trace this trialectic, the author uses Ebrahim Moosa's theoretical framework of